Association between indoor air pollutant exposure and blood pressure and heart rate in subjects according to body mass index - Jung, Chien-Cheng; Su, Huey-Jen; Liang, Hsiu-Hao (The Science of the total environment, 2016)
This study investigates the effects of high body mass index (BMI) of subjects on individual who exhibited high cardiovascular disease indexes with blood pressure (BP) and heart rate (HR) when exposed to high levels of indoor air pollutants. We collected 115 office workers, and measured their systolic blood pressure (SBP), diastolic blood pressure (DBP) and HR at the end of the workday. The subjects were divided into three groups according to BMI: 18–24 (normal weight), 24–27 (overweight) and >27 (obese). This study also measured the levels of carbon dioxide (CO2), total volatile organic compounds (TVOC), particulate matter with an aerodynamic diameter less than 2.5μm (PM2.5), as well as the bacteria and fungi in the subjects' work-places. The pollutant effects were divided by median. Two-way analysis of variance (ANOVA) was used to analyze the health effects of indoor air pollution exposure according to BMI. Our study showed that higher levels of SBP, DBP and HR occurred in subjects who were overweight or obese as compared to those with normal weight. Moreover, there was higher level of SBP in subjects who were overweight or obese when they were exposed to higher levels of TVOC and fungi (p<0.05). We also found higher value for DBP and HR with increasing BMI to be associated with exposure to higher TVOC levels. This study suggests that individuals with higher BMI have higher cardiovascular disease risk when they are exposed to poor indoor air quality (IAQ), and specifically in terms of TVOC. [Display omitted] •Obese populations have high SBP values when they exposure to high TVOC and fungi.•There are higher DBP and HR levels with increasing BMI and exposure to TVOC level.•Obese population have higher heart diseases risk when they exposure to poorer IAQ.